Angular analysis of charged and neutral B → K[mu]+[mu]− decays - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Fontana, Marianna; et al. (Journal of high energy physics, 2014)
The angular distributions of the rare decays B+ → K+μ+μ− and $ {B^0}→ K_{S}^0{μ^{+}}{μ^{-}} $are studied with data corresponding to 3fb−1 of integrated luminosity, collected in proton-proton collisions at 7 and 8 TeV centre-of-mass energies with the LHCb detector. The angular distribution is described by two parameters, FH and the forward-backward asymmetry of the dimuon system AFB, which are determined in bins of the dimuon mass squared. The parameter FH is a measure of the contribution from (pseudo)scalar and tensor amplitudes to the decay width. The measurements of AFB and FH reported here are the most precise to date and are compatible with predictions from the Standard Model.
The LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Färber, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, M. Neuner, T. Nikodem, M. Schmelling, P. Seyfert, S. Stahl, U. Uwer, M. Vesterinen, H. Voss, S. Wandernoth, D. Wiedner, A. Zhelezov [und viele weitere]
Im Titel sind das Plus- und das Minuszeichen hochgestellt
Im Titel ist "mu" als griechischer Buchstabe dargestellt
Gesehen am 21.09.2020